Retrograde Intubation as an Alternative Approach to Failed Video-Assisted and Fiber Optic Laryngoscope in Patient with Predicted Difficult Intubation: Case Report - Dananjaya, Vigyan; Suparno Adi Santika; Robeth Ardyansyah, Rizky; Salma Auliya Syahida (Fakultas Kedokteran Universitas Brawijaya, 2025)
Difficult intubation is a challenge for an Anesthesiologist. Expertise in effective airway management which includes initial assessment to follow-up care. In this article we reported a 58-year-old male with a history of tracheostomy, craniotomy, and Open Reduction and Internal Fixation (ORIF) placement on the maxilla dextra, who will undergo a cranioplasty procedure under general anaesthesia. On physical examination, a mallampati class IV assessment was obtained, the distance between incisors < 3 fingers. The pre-anesthesia assessment an American Society of Anesthesiologist (ASA) II with LEMON score of 4. The intraoperative process used intravenous induction with fentanyl 150 mg, midazolam 5 mg, Propofol 150 mg, and Rocuronium 50 mg. Two airway management scenarios in this patient failed, which were video-assisted laryngoscopy and fibre optic laryngoscopy, therefore a third scenario was performed using retrograde intubation technique. Retrograde intubation is an effective alternative in patients with intubation difficulties.